A Comprehensive Review of the Phytochemistry and Therapeutic Efficacy of Viola yedoensis Makino - Shuang Wang; Congcong Shen; Shengyu Zhang; Han Di; Yanhong Wang; Feng Guan (Molecules)
Viola yedoensis Makino (V. yedoensis), a perennial herb in the Violaceae family, is recognized for its violet flowers and has a longstanding role in ethnomedicine for treating various inflammatory diseases, such as boils, furuncles, carbuncles, and both acute and chronic hepatitis, among others. A comprehensive literature review was conducted utilizing resources including the Chinese Pharmacopoeia, Flora of China, Web of Science, PubMed, Baidu Scholar, Google Scholar, and China National Knowledge Infrastructure (CNKI). This paper serves as the inaugural comprehensive review of the latest findings regarding the botany, traditional applications, phytochemistry, pharmacological properties, quality control, and prospective uses of V. yedoensis. The objective is to provide a robust foundation for future research and to suggest novel avenues for exploring its potential applications. To date, 162 chemical constituents have been isolated from V. yedoensis, with flavonoids and coumarins identified as particularly abundant. These compounds exhibit promising activities, including anti-inflammatory, anti-pyretic, anti-viral, anti-tumor, anti-lung injury, anti-liver injury, anti-bacterial, anti-coagulant, anti-complement, and anti-oxidant properties. Despite considerable advancements in fundamental research on V. yedoensis, further investigations are required to elucidate the underlying mechanisms of action and to discover additional uncharacterized compounds. This review underscores the plant’s significant development potential, highlighting the necessity for more in-depth exploration.